The problem of changes in the structure of a sound propagating in a room in the aspect of multidimensional space - OZIMEK, Edward (Archives of Acoustics, 1987)
A change in the amplitude-frequency structure of sound in a room is a complex physical phenomenon depending on a number of acoustic properties of the interior. The essence of this change consists in the influence of the acoustic parameters of the room on the spectral-temporal course of the sound propagating in it. The starting point of the undertaken studies was to represent the changes in the sound structure in the room based on the relations occurring between the elements of two sets, P and S. All the possible acoustic states of the room were subordinated to the elements of the set P, thus gaining the so-called space of states. On the other hand, all the possible changes in the sound structure were subordinated to the elements of the set S, thus achieving the so-called space of the signal structure. Analysis of the relation occurring between these two spaces showed that physical changes in the sound structure in a room could be mapped in a space of subjective sensations with coordinates being the corresponding psychoacoustic quantities. Such a mapping can be an important step towards the determination of the common plane of objective and subjective evaluations of the acoustic quality of a room, which is still looked for in the problems of room acoustics.